Visualisation of Studies on Knee Injuries in Football: A Bibliometric Analysis - Yildiz, Muhammed (Sportverletzung · Sportschaden, 2024)
Football is a popular sport on a global scale, and injuries sustained by football players have become a significant concern for sports physicians and researchers. Among these injuries, knee injuries are a commonly encountered problem in football players with long-term effects. This paper aims to perform a visual mapping and a bibliometric analysis of research on knee injuries in football, examining the current state and research trends. For this purpose, all publications from the Social Sciences Citation Index (SSCI), Science Citation Index Expanded (SCIE), Emerging Sources Citation Index (ESCI), and Arts & Humanities Citation Index (AHCI) within the Web of Science database were analysed. VOSviewer 1.6.18 was utilised for visualising bibliometric data. A total of 2159 publications were included in the study. The analysis covers publication year, authors, citation counts, and distributions among publishing journals. Authors, institutions, and international relationships were investigated, and keyword analysis, bibliometric coupling, and co-citation network analyses were conducted. The findings reveal that the United States and Australia are the countries with the highest number of publications. From 2018, there has been a noticeable increase in the number of publications. Citation and publication counts reached their peak in 2021. Turkey takes the 28th rank in terms of citation and centrality. The keywords “soccer,” “football,” “knee”, and “anterior cruciate ligament” were found to be intensively used with high centrality. In conclusion, visual mapping through bibliometric analysis highlights the magnitude and diversity of research in the field of knee injuries in football. It emphasises the need for further studies in this area for future researchers, shedding light on important research areas. Moreover, it provides insights into the prevention of such injuries in football players and the development of effective treatment strategies by fostering more knowledge and understanding of knee injuries.
Keywords: Bibliometric Analysis; Football; Knee Injury; Sports Medicine; Visualisation